1992
DOI: 10.1111/j.1939-1676.1992.tb00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Secreting Pancreatic (Islet Cell) Carcinoma in a Cat

Abstract: A functional, insulin-secreting pancreatic (islet cell) carcinoma was diagnosed in a 17-year-old male Siamese cat. Diagnosis was made on the basis of clinical signs (i.e., seizures and stupor) that resolved temporarily after correction of hypoglycemia with feeding or intravenous administration of glucose, the finding of an inappropriately increased serum insulin concentration in the face of hypoglycemia, and prolonged resolution of hypoglycemia after surgical removal of the tumor. Primary islet cell tumor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 4 publications
5
58
0
1
Order By: Relevance
“…Insulinoma is an uncommon tumor of cats. Previous reports of feline insulinoma have focused on clinical and histological features of these tumors 1–5 . In the current study, immunohistochemical analysis demonstrated the production of multiple peptide hormones by the tumor cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Insulinoma is an uncommon tumor of cats. Previous reports of feline insulinoma have focused on clinical and histological features of these tumors 1–5 . In the current study, immunohistochemical analysis demonstrated the production of multiple peptide hormones by the tumor cells.…”
Section: Discussionmentioning
confidence: 58%
“…Insulinomas in cats are rare, with fewer than a dozen well‐documented cases reported in the literature. In cats, the reported clinical signs usually are related to tumor functional capacity and include lethargy, weakness, and seizures 1–5 …”
mentioning
confidence: 99%
“…Commonly affected breeds include Boxers, German Shepherds, Irish Setters, Poodles, Fox Terriers, Collies, and Labrador Retrievers, but these results may be biased by the popularity of several of these breeds (Goutal et al, 2012). These tumors are identified with some frequency in the ferret and rarely in the cat (Capen, 2002;Hawks et al, 1992). The cytologic appearance of insulinomas is typical of other endocrine tumors.…”
Section: Tumors Of the Endocrine Pancreasmentioning
confidence: 99%
“…Insulin-secreting beta-cell tumors are rare in cats with only a few single cat case reports in the literature (McMillan, 1985;O'Brien et al, 1990;Hawks et al, 1992;Kraje, 2003;Greene and Bright, 2008) and one additional report in which the beta-cell tumor was an incidental finding at necropsy in a cat with ductal pancreatic adenocarcinoma (Carpenter et al, 1987). We have seen only two cats with beta-cell neoplasia during the past three decades, in contrast to more than 150 dogs with the disease during the same time interval.…”
Section: Insulin-secreting Beta-cell Tumors In Catsmentioning
confidence: 99%